The viewserver hierarchy for interdomain routing protocols and evaluation. - Alaettinoglu, C. (IEEE Journal on selected areas in communications)
We present an interdomain routing protocol based on a new hierarchy, referred to as the viewserver hierarchy. The protocol satisfies policy and type of service (ToS) constraints, adapts to dynamic topology changes including failures that partition domains, and scales well to a large number of domains without losing detail (unlike the usual scaling technique of aggregating domains into superdomains). Domain-level views are maintained by special nodes called viewservers. Each viewserver maintains a view of a surrounding precinct. Viewservers are organized hierarchically. To obtain domain-level source routes, the views of one or more viewservers are merged (up to a maximum of twice the levels in the hierarchy). We also present a model for evaluating interdomain routing protocols, and apply this model to compare our viewserver hierarchy against the simple approach where each node maintains a domain-level view of the entire internetwork. Our results indicate that the viewserver hierarchy finds many short valid paths and reduces the amount of memory requirement by two orders of magnitude